1993
DOI: 10.1007/bf00021732
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to turnip mosaic virus in Chinese cabbage

Abstract: Turnip mosaic virus (TuMV) is the most important virus of commercially grown cole crops in many Asian countries, affecting both yield and quality. TuMV-infected Chinese cabbage becomes unmarketable because of the presence of black spots and necrosis often induced by the virus . Resistance breeding is complicated by the existence of five strains of the virus, one of which was discovered in 1985 for the first time in Taiwan . Resistance to strains C1 to C3 is readily available among the Chinese cabbage germplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…This study showed that inheritance of TuMV resistance in Chinese cabbage is controlled by a dominant gene, which is consistent with the findings of Niu () and Yan (), although inconsistent with those of Yoon et al. (), Han (), Qian et al. () and the conclusions of our previous study (Li et al.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This study showed that inheritance of TuMV resistance in Chinese cabbage is controlled by a dominant gene, which is consistent with the findings of Niu () and Yan (), although inconsistent with those of Yoon et al. (), Han (), Qian et al. () and the conclusions of our previous study (Li et al.…”
Section: Discussionsupporting
confidence: 56%
“…Yoon et al. () used the resistant material ‘0–2’, which showed resistance to each of the TuMV strains C1 to C5, to study the inheritance of TuMV resistance in Chinese cabbage, and they concluded that the resistance to both TuMV‐C4 and TuMV‐C5 is controlled by two recessive genes. Using the same resistant material (‘0–2’) and different susceptible materials, Suh et al.…”
Section: Discussionmentioning
confidence: 99%
“…Results of genetic analysis for TuMV resistance were not exactly consistent. Some showed that the resistance of TuMV was controlled by two (Niu et al 1984;Suh et al 1995) or one (Suh et al 1995;Yan 2000;Wang 2004;Gao et al 2008) dominant genes, while studies by Yoon et al (1993) and Han (2003) showed that TuMV resistance in Chinese cabbage was controlled by one (the latter) or two (the former) recessive genes. Reports by Rusholme et al (2007) indicated that a recessive gene retr01 and a dominant gene ConTR01 controlled resistance to TuMV isolate CDN 1 and CZE 1 in Brassica rapa (Chinese cabbage), and the first gene was epistatic to the second one.…”
Section: Inheritance Of Tumv Resistancementioning
confidence: 99%
“…Recently identified resistances in Brassica rapa appear to be effective against a broad range of TuMV isolates (Suh et al 1995;Hughes et al 2002;. Several different modes of inheritance of TuMV resistance in B. rapa have been described (Yoon et al 1993;Suh et al 1995;Hughes et al 2002;. In contrast, predominantly dominant resistance has been identified in Brassica napus (Shattuck and Stobbs 1987;Walsh 1989;Walsh et al 1999;Jenner et al 2002).…”
Section: Introductionmentioning
confidence: 99%